Model of Implementation of Integration of Islamic Religious Education and Science at MAN 2 Model Medan - Dalimunthe, Aldi Wijaya; Salminawati, Salminawati; Dahlan, Zaini (SAINTIS Publishing, 2024)
The Research and Development and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia has instructed every madrasah unit to integrate science because madrasahs have a mission of integrating science, MAN 2 Model Medan as a pilot madrasah in North Sumatra certainly implements integration but the pattern and model of integration applied are not yet known. The purpose of this study is to describe and analyze the understanding of MAN 2 Model Medan policy makers about the integration of Islamic religious education and science and to determine the planning, implementation and model of integration of Islamic religious education and science at MAN 2 Mode Medan . The type of research used by the researcher is qualitative research. The researcher conducted observations and collected data naturally without manipulating the subjects studied. The researcher used data collection techniques by means of observation, observation, interviews and documentation. While the data analysis technique by means of data reduction, data presentation and drawing conclusions of data takes place and after the completion of data collection in a certain period, in the form of all written or oral data from people and observed behavior. Based on the research results, it was found that: 1) The understanding of MAN 2 Model Medan policy makers regarding the concept of integrating Islamic religious education and science does not yet have original administrative guidelines. However, policy makers continue to implement the integration of Islamic religious education and science with the guidelines of the independent curriculum, namely KMA No. 437 of 2022 and its renewal in KMA No. 450 of 2024; 2) Planning the integration of Islamic religious education and science in learning through annual independent curriculum workshops and MGMP meetings and planning P5RA activities; 3) Implementation of the Integration of Islamic religious education and science through several activities, namely teaching and learning activities, extracurricular activities, Madrasah Science Competition (KSM) activities, P5RA activities and superior activities of the MAN 2 Model Medan Dormitory; 4) The model for the integration of Islamic religious education and science at MAN 2 Model Medan is the integration of scientific materials (Religion, Science and social) and integration through the instillation of Islamic studies in various madrasah activities